Beban Masyarakat Adat Menghadapi Hukum Negara - Syamsudin Syamsudin (Fakultas Hukum Universitas Islam Indonesia, 2008)
The most common type of conflict involving indigenous people is the dispute on the ownership of economic resources and cultural sites which are convicted and is guaranteed as traditional indigenous rights. In this regard, indigenous people stand vis a vis with investors’ interest which is usually safeguarded by state legal instruments. Indigenous people are shaky in this kind of conflict, and in the factual cases, the process to weaken and destroy indigenous community has been made through regulations, policies as well as the real actions made by the government.